Korelasi Parental Bonding Dan Self-Esteem Dengan Perilaku Seksual Pada Remaja Usia Pertengahan Di SMA Parulian 1 Medan - Hutapea, Clarissa; Tambunan, Dior Manta (Universitas Murni Teguh, 2024)
Emotional parental attachment that occurs between parents and their offspring (Parental Bonding) as well as individual Self-Esteem is one of the possible factors in the development of adolescent sexual behavior. The lack of parental role is considered to influence the increase in sexual behavior. The purpose of this study was to explore the relationship between parental bonding and self-esteem with sexual behavior in middle-aged adolescents at Parulian 1 Senior High School Medan. The method used quantitative methods with a cross sectional approach. The sample size was selected using a total sampling technique of 147 respondents. The relationship between variables was analyzed using the Spearman Rho statistical test. The results of study research shows that Parental Bonding has a significant relationship with adolescent sexual behavior with p-value < 0,005, but Self-Esteem does not have a significant relationship with adolescent sexual behavior with p-value > 0,005. It is recommended for future researchers to add the variables such as parenting patterns, peer influence, pornographic media influence, and knowledge.